Invisible Divide: Farm Workers and Telephone Accessibility - James I. Grieshop; Viviana Delgadillo; Nicolas Flores; Debora Ramirez (Journal of Applied Communications, 2003)
Telephones are almost universally available throughout the United States. However, farm workers and their families lack ready access to this technology. A small sample of California farm workers, vendors of telephone technology, and farm camp managers were interviewed to help understand farm worker access to and use of telephones. Results revealed a pattern of low access to and availability of telephones and major problems in the use of pre-paid phone cards. The authors argue that such communities are largely forgotten and seemingly invisible in discussions of the digital divide. Similar situations likely exist in most farm worker communities throughout the country.